Efektivitas Penggunaan E-Learning Berbasis Kahoot! Course untuk Meningkatkan Hasil Belajar Siswa di SMA Negeri 1 Cigugur - Handayani, Nadia; Fitriah Nurjanah, Hifni (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to evaluate the effectiveness of using Kahoot! Course in improving the learning outcomes of Sociology subject for XI social studies class students at SMA Negeri 1 Cigugur. The background of this study is the low motivation of students to learn and the limited variety of learning methods used by teachers, so that technology-based learning media is needed that can bring interactivity and active involvement of students. The research used a quantitative approach with a pretest-posttest control group design. The research instruments were learning outcome tests and motivation questionnaires given before and after treatment. The analysis showed that the experimental group who learned using Kahoot! Course had a significant increase in academic achievement compared to the control group that used conventional methods. In addition, the questionnaire data showed an increase in student motivation and enthusiasm for learning in the experimental group. This finding confirms that Kahoot! Course is effective as an interactive learning media that not only improves learning outcomes, but also encourages students' active participation. The implication of this research recommends the integration of technology-based media such as Kahoot! Course in learning Sociology and other subjects to create a more interesting, collaborative, and meaningful learning atmosphere.